Homozygous familial hypercholesterolemia with corneal arcus: A rare case report - Bablu Kumar Gaur (Indian Journal of Paediatric Dermatology, 2020)
We report here a case of an 11-year-old adolescent boy who presented with asymptomatic multiple yellowish skin lesions and corneal arcus. A family history of similar complaints was present in the elder male sibling who died with underlying coronary artery disease. Laboratory findings and family history were consistent with homozygous familial hypercholesterolemia. He was started on lipid-lowering drugs and is under regular follow-up. Early diagnosis and timely initiation of treatment helped to save the affected individual and the other family members.